PENERAPAN FUNGSI MANAJEMEN DAN ANALISIS FINANSIAL BUDIDAYA BAWANG PUTIH (Studi Kasus Petani Bawang Putih Di Desa Cipendawa, Pacet, CianjurJawa Barat) - Tri Waluyo (Universitas Nasional, 2020)
Efficient farming management will bring positive income or a profit, inefficient farming will bring a loss. Efficient farming is farming that has high productivity. This can be achieved if the farm management is well managed. Through the application of good management, it is hoped that the results of the farming will also be good. This management ability is important because farming is not merely a way of life. More than that, it is a company. One of the ups and downs of a company is influenced by its management ability. The research was conducted in Cipendawa Village, Pacet, Cianjur, West Java from March-May 2019. The respondents interviewed were garlic farmers. The data can be tabulated and processed using financial analysis tools by looking at the R / C ratio and the payback period. This research is a case study conducted at Gapoktan Multi Tani Jaya Giri. Sampling was carried out randomly (random) and a sample of 13 respondents who did garlic farming either monoculture or intercropping. Data were analyzed with a basic quantitative formula consisting of revenue analysis and calculation of R / C ratio. The application of management functions in an effort to empower farmers requires group management carried out from, by and for farmers. In management there are several main functions consisting of planning, organizing, mobilizing, monitoring and assessing. Management is needed to organize farmer groups in making / taking decisions in organization. The results of the analysis show that the largest average income is found in garlic farming with an intercropping pattern of Rp. 33,903,475 and for a monoculture cropping pattern of Rp. 15,644,568. The R / C ratio in garlic farming with a monoculture cropping pattern was 1.71, while the R / C ratio for garlic farming with an intercropping cropping pattern was 2.17. The largest R / C ratio value is found in the intercropping cropping pattern with an R / C ratio of 2.17. This shows that white onion farming using the intercropping pattern is more profitable than the monoculture cropping pattern.